Los impactos de la transferencia del manejo del riego en el Distrito de Riego Alto Rio Lerma, Mexico. In SpanishImpact assessment of irrigation management transfer in the Alto Rio Lerma Irrigation District, Mexico - Kloezen, W.H.; Garcés-Restrepo, C.; Johnson, S.H. (International Water Management Institute, 1998)
Tests the hypothesis that, in general, irrigation management transfer has positive impacts on operation performance, managerial accountability, O&M budgeting and expenditures, costs of water to farmers, and agricultural and economic productivity in the Alto Rio Lerma Irrigation District in Mexico. Evaluates the potential of the Mexican IMT process as a model for other countries.